Ecological Planning in Built Environment - Vasileios Galifianakis (European Regional Science Association (ERSA), 2006)
The downgrade of natural environment in the last decades is obvious and the source of problem is located in urban centers. Respectively, the solution of the problem should be sought there. The ecological urban planning aims at the upgrade of urban space, redefining its relationship with residents. The present article methodizes the approach to the ecological urban planning and it is one of the there are too. Particularly, it essays an approach to the ecological urban planning through the management of those elements that compose the operation of a city and concerns the management and the control of green space, energy, water, transports, litter and society. In this way, a catholic consideration and management of the urban space, as well as a set of policies and actions for its upgrade, is achieved. Furthermore, specific references to examples in Greece – problems and perspectives – are made. Coinstantaneously, the study of international and European cities that have achieved a high level of quality of life is the proof that the ecological city does not constitute a utopia, but a challenge for the society, the planners, the local governments and the residents-users. Finally, the institutional frame and the policies, that support the ecological urban planning, are analyzed, as these are the base for its implementation.
Keywords: 330